HUBUNGAN KEPATUHAN DIET DENGAN KEJADIAN KOMPLIKASI PADA PENDERITA HIPERTENSI DI RUANG RAWAT INAP DI RS. BAPTIS KEDIRI - Wahyuningsih, Aries; Wibowo, Adek (Jurnal Penelitian STIKES Kediri, 2011)
ABSTRACT Â Hypertension or high blood pressure is a condition which systolic blood pressure is higher than140 mmHg and diastolic is higher 90 mmHg. Patient with hypertension, who does not get good treatment, would suffer kinds of complicated diseases such as coronary heart disease, heart failure, CVA, renal failure, retinopathy. Hypertension can be controlled by changing life style especially diet and physical activity as well as medicine (oral and infection). The objective of this research is to analyze correlation between diet obedience and complicated incident to patient with hypertension in wards Kediri Baptist hospital. Â Â Â Â Â Â Â Â Â Â Â The design of this research was analytic correlation research that explains a relation, predict, test based on existed theory. The populations were patients with hypertension in wards Kediri Baptist Hospital that met criteria inclusion. The samples were 26 respondents using simple random sampling. The independent variable was diet obedience to patient with hypertension and the dependent variable was complication incident to patient with hypertension. Data was analyzed statistically using â€œMann-Whitney testâ€ with significant level Î± â‰¤ 0.05. The result showed that respondent had high diet obedience, there were 10 respondents (38%) and more than 50% respondent had no complication, there were 17 respondents (65%). Statistical analysis of Mann- Whitney showed p=0.000. It could be concluded that there was correlation between negative diet obedience and complication incident to patient with hypertension. It is necessary to develop about other factors that influence the obedience in running low salt diet, maintaining of body weight and avoiding obesity, smoke, and alcohol to patient with hypertension. Â keywords: Obedience, complication, hypertension.